Two-phase changes in workability of sand-bentonite mixture triggered by seawater and binder during seepage cut-off wall construction in marine environment - Ting, Matthew Zhi Yeon (2023)
Phenomenal sea level rise is exacerbating the risk of seawater intrusion in coastal areas, especially those with sandy soil, causing land erosion. Seepage cut-off walls made of in-situ sand, bentonite and binder can be employed. However, the presence of salts in soil is detrimental to water retention ability of bentonite, which can be aggravated by binder-induced cation exchange reactions, causing constructability issues for two-phase cut-off walls. Therefore, this study aims to evaluate the workability properties, including flowability and bleeding of sand-bentonite-binder mixture in seawater environment. The mechanism of decrease in water retention of bentonite has been investigated using Atterberg limits, X-ray diffration (XRD) and scanning electron microscope (SEM) analyses. In phase-one construction, seawater significantly increased flowability of sand-bentonite mixture. During the second phase, binder inclusion increased flowability even further. Given comparable flowability, the bleeding in sand-bentonite-binder mixture containing seawater was much greater than in the non-seawater environment. This was ascribed to a loss in water retention capacity of bentonite, in which external cations from seawater and binder exchanged with bentonite, resulting in reduction in liquid limit. The Na-based montmorillonite was transformed into Ca-based montmorillonite, causing the morphology of bentonite particles to flocculate. Despite this, the study discovered a feasible sand-bentonite-binder mixture including reactive magnesia (MgO)-activated ground granulated blast-furnace slag (GGBS) and seawater-resistant bentonite, which impeded the increase in workability.